Reduction and oxidation performance evaluation of manganese-based iron, cobalt, nickel, and copper bimetallic oxide oxygen carriers for chemical-looping combustion. (5th January 2018) - Sub Kwak, Byeong; Park, No-Kuk; Ryu, Ho-Jung; Baek, Jeom-In; Kang, Misook
Graphical abstract: Redox reaction on the Cua-Mnb-Ox for the chemical looping combustion. Highlights: Redox performance for Ma-Mnb-Ox (M = Fe, Co, Ni, and Cu) investigated in detail. The highest redox performance (16.7 wt%) was observed for Cu2.0-Mg1.0-Ox. The Cu2.0-Mn1.0-Ox sample was stable up to 10 reaction cycles. Abstract: Transition metal oxides like Fe2 O3, Co3 O4, NiO, and CuO have mainly been used in the chemical-looping combustion (CLC) reaction as oxygen carrier particles because of their outstanding performances due to high reduction potential. However, monometal oxides have a serious problem of rapid deactivation due to agglomeration between each particle after several redox cycles. In order to solve this problem, bimetal oxides based on Mn, which undergoes no deactivation, were synthesized. Mn-based bimetal oxygen carrier particles Fea-Mnb-Ox, Coa-Mnb-Ox, Nia-Mnb-Ox, and Cua-Mnb-Ox were synthesized by using a sol–gel method. The range of a and b in the particle label obtained in this study is 0.5–2.5, depending on the metal content added. The chemical and physical properties of the prepared particles were examined using X-ray diffraction (XRD), scanning electron microscopy (SEM), CH4 -/CO-temperature programmed desorption, and thermogravimetric analysis (TGA). The XRD results showed that the prepared particles comprised two- or three-phase mixed metal oxides. The Fe2.0-Mn1.0-Ox particle was in the phases of Fe2 Mn1 O4 and Fe20.16 Mn11.84 O48, respectively, and the Co2.0-Mn1.0-Ox particle had the phase of Co2 Mn1 O4 . In addition, Ni2.0-Mn1.0-Ox particle has NiO and Ni1 Mn2 O4 phases, and Cu2.0-Mn1.0-Ox particle exist in the phases of CuO, Cu2 O and Cu1 Mn1 O2, respectively. The distributions of added elements on the particles were observed from the SEM mapping results. The oxygen carrier capacities of the particles were tested by isothermal H2 /air and CH4 /air redox cycle experiments using TGA at 850 °C. The improved results obtained in this study revealed that the Cu2.0-Mn1.0-Ox particle was an enhanced bimetal oxide oxygen carrier for CLC under CH4 /air conditions. In particular, among the synthesized particles, the Cu2.0-Mn1.0-Ox particle stably showed 16.7 wt% oxygen transfer capacity over 10 redox cycle under CH4 /air at 850 °C.